La noción del tiempo en la obra poética de Jorge Luis Borges y César Vallejo. - Barboza Ramírez, María Isabel (2012)
The following article departs from the notion of time in the poetic works of Borges and Vallejo. It is based in a comparative study between the lyrical productions of both authors. Borges as well as Vallejo propose us a transgressed image of time through different types of linguistic and conceptual disruptures.